Co-teaching in information literacy during work placements: the librarian’s role - Kolstad, Anett Kristin (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2015)
Introduction: This article presents findings from a development project designed to improve Information Literacy (IL) education by linking it to nursing students’ application of evidence-based practice during work placements. The Learning Centre at Oslo University College in Norway aimed to find out, what interactions and conditions influenced the librarian’s role in the context of interdisciplinary supervision of nursing students’ assignments and the development of a common supervision culture. Research Design: The librarian involved in the initiative had a dual role as both researcher and practitioner. Besides direct experiences from being a participant in the project, the empirical material consists of observation notes, meeting notes, presentations, guideline in IL, e-mails, an interview, 285 comments from students, nurse educators, nurse supervisors and librarians, through blog and the Wiki Learning Management System (LMS). The evidence on which this article is based involved analysis of both oral and written communication, framed in practice-oriented approaches. Findings: The conditions influencing the changing position of the librarian from an ‘outsider’ to becoming a member of the community of practice with common structures for the collaboration and supervision included meetings, a blog and a Wiki. Multidisciplinary, complementary skills in the supervision teams provided improved quality of supervision and led to a new joint supervision community. Conclusion: Together with the nurse educators and the nurse supervisors, the librarian was able to be a partner and a catalyst of IL workplace learning. The LMS was a decisive tool in the process. However, to be successful, this changed role for the librarian may require further pedagogical training and expertise in the development of interdisciplinary educational supervision.